Theme Of The Festival And Student Interest In Participating In The Student Film - Setyawan, Deddy; Widyastutieningrum, Sri Rochana; Handriyotopo, Handriyotopo (Journal of Urban Society's Arts, 2023)
This research aims to analyze the relationship between film festival themes and students' interest in participating in the Jogja Student Film Festival (FFPJ). On the one hand, the theme of a film festival provides guidance about the films that will be competed in the festival, on the other hand, the theme can also limit students' freedom in expressing ideas or ideas through film works. Restrictions on a theme may reduce interest in participating in the festival. This research uses descriptive qualitative methods. Data was taken from interviews and FFPJ documents from 2010 - 2021. Data analysis was descriptive qualitative. The research results show a clear pattern trend, namely the relationship between themes and the number of film works included in FFPJ. When FFPJ has a free theme, the number of film works tends to increase. When FFPJ has a theme determined by the organizer, the number of films included in FFPJ decreases. Students seem to prefer making films to express their ideas or concepts according to their themes rather than having to make films according to the themes desired by the organizers.